Educational problems facing teachers of natural sciences in the course system for the secondary stage in Qassim - Al Harbi, Abdullah bin Maatak bin Musleh (Journal of Educational and Psychological Sciences, 2017)
The objective of the research is to identify the teaching problems facing natural science teachers in the secondary school curriculum in Qassim region, from their point of view, using the analytical descriptive approach, which includes a questionnaire tool designed to achieve the research objectives. Chemistry, Biology). The results of the study reached 5 axes with a high response rate, which is a descending order: the problems related to the teacher at an average of 4.00, then the student average of 3.87, the educational activities with an average of 3.77, the teaching methods with an average of 3.55, Then the calendar is averaged (3.53). The results showed that there were statistically significant differences in the assessment of the research sample to the extent of the problems of teaching, according to the variable of specialization for the benefit of the chemistry teachers, according to the years of experience in favor of the teachers. With less experience. While there were no statistically significant differences according to the type of scientific qualification. In light of the results of the research, a number of recommendations were presented that could contribute to solving the research problems. Finally, a series of future studies were presented.